The question of equivalence for generalized Hausdorff matrices - Albayrak, Inci; Rhoades, B. E. (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2007)
In the present paper we investigate when Hausdorff matrices and generalized Hausdorff matrices, with the same mass function, are equivalent, as bounded operators on c and l(P). (c) 2006 Elsevier Inc. All rights reserved.
Keywords: equivalence; generalized Hausdorff matrices; Hausdorff matrices; Mathematics